Development and comparison of HPLC and MEKC methods for the analysis of cyclic sulfur mustard degradation products. Issue 7 (30th January 2017) - Lees, Heidi; Vaher, Merike; Kaljurand, Mihkel
Abstract : In this study, novel, fast, and simple methods based on RP‐HPLC and MEKC with DAD are developed and validated for the qualitative and quantitative determination of five cyclic sulfur mustard (HD) degradation products (1, 4‐thioxane, 1, 3‐dithiolane, 1, 4‐dithiane, 1, 2, 5‐trithiepane, and 1, 4, 5‐oxadithiepane) in water samples. The HPLC method employs a C18 column and an isocratic water‐ACN (55:45, v/v) mobile phase. This method enables separation of all five cyclic compounds within 8 min. With the CE method, the baseline separation of five compounds was achieved in less than 11 min by applying a simple BGE composed of a 10 mM borate buffer and 90 mM SDS (pH 9.15). Both methods showed good linear correlation ( R 2 > 0.9904). The detection limits were in the range of 0.08–0.1 μM for the HPLC method and 10–20 μM for MEKC. The precision tests resulted in RSDs for migration times and peak areas less than 0.9 and 5.5%, respectively, for the HPLC method, and less than 1.1 and 7.7% for the MEKC method, respectively. The developed methods were successfully applied to the analysis of five cyclic HD degradation products in water samples. With the HPLC method, the LODs were lowered using the SPE for sample purification and concentration.